2009
DOI: 10.1590/s0103-50532009000200014
|View full text |Cite
|
Sign up to set email alerts
|

Proposal of an EPR based method for pollution level monitoring in mangrove sediments

Abstract: O objetivo deste estudo foi o de monitorar o nível de poluição de sedimentos subaquáticos de florestas de mangue utilizando espectroscopias de ressonância paramagnética eletrônica (EPR) e de infravermelho próximo (NIR) e análises químicas. A espectroscopia de EPR foi útil para determinar a presença de radicais livres orgânicos de semiquinonas, bem como, fornecer informações sobre a presença de ferro trivalente em domínios diluídos e concentrados nos espectros das amostras. Concluiu-se que, o uso de EPR e NIR, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…The oxidation of high quantities of organic matter by the action of microorganisms can result in conditions that are more reduced. In a polluted environment, certain microorganisms can oxidize organic pollutants and then reduce Fe(III) solid phases to more soluble Fe(II) (Mangrich et al, 2009). This was confirmed using kappa coefficient analysis applied to the EPR results, total AHs, and total PAHs.…”
Section: Comparison Among Different Techniques For Sedimentary Hydrocmentioning
confidence: 64%
See 3 more Smart Citations
“…The oxidation of high quantities of organic matter by the action of microorganisms can result in conditions that are more reduced. In a polluted environment, certain microorganisms can oxidize organic pollutants and then reduce Fe(III) solid phases to more soluble Fe(II) (Mangrich et al, 2009). This was confirmed using kappa coefficient analysis applied to the EPR results, total AHs, and total PAHs.…”
Section: Comparison Among Different Techniques For Sedimentary Hydrocmentioning
confidence: 64%
“…The ANT core presented more features at magnetic fields above 3000 G (Fig. 7, Ib, 6e8 cm and 23e25 cm sections), indicative of a reduced environment (Mangrich et al, 2009), while PC3 revealed a clear distinction between the ANT and PGA sediments. These data suggested that the sediments at the PGA site were more oxidized, compared to those at the ANT site.…”
Section: Electron Paramagnetic Resonance (Epr)mentioning
confidence: 96%
See 2 more Smart Citations
“…As this technique is suitable for volatile elements, the authors presented a procedure to generate volatile Co, producing a complex between this element and sodium diethyldithiocarbamate (DDTC). Mangrich et al 139 combined several techniques, such as electron paramagnetic resonance (EPR), near-infrared spectroscopy and chemical elemental analyses, for pollution level monitoring in mangrove sediments. Using EPR it was possible to nondestructively assess the environmental pollution level of coastline.…”
mentioning
confidence: 99%